Smart Mobility: Mobility Services in Urban Area a Literature Review - Fathoni, Fikri; Prasetyo, Yuli Adam; Mukti, Iqbal Yulizar; Santoso, Ari Fajar (STKIP PGRI Tulungagung, 2025)
Smart mobility is one of the important aspects for cities to imple-ment the smart city concept. smart mobility is the use of information technology for urban transportation systems in order to create inte-grated, effective, sustainable, easily accessible transportation ser-vices to support mobility, and improve the quality of life of urban communities. The main focus of this research is to answer the re-search questions in order to compile and present a comprehensive understanding of the concept of intelligent mobility, with an empha-sis on the latest developments and implementations of intelligent mobility in the scientific literature. This research uses the Systemat-ic Literature Review method to identify terminology, services, func-tions, and technologies, that are elements in the implementation of smart mobility. There are 30 previous research articles with publica-tion years 2018-2023 on smart mobility that contribute to this litera-ture review. The results of this literature review provide in-depth insights into how information and communication technologies can improve sustainability and efficiency in urban transportation sys-tems. By understanding previous research, this research provides a solid basis for the development and implementation of the concept of smart mobility.